Regulation of synthesis of lactosylceramide and long chain bases in normal and familial hypercholesterolemic cultured proximal tubular cells - Chatterjee, S; Clarke, K S; Kwiterovich, P O (The Journal of biological chemistry, 1986)
We have investigated the effects of lipoproteins on sphingolipid metabolism in proximal renal tubular cells from normal subjects and low density lipoprotein (LDL) receptor-negative homozygous familial hypercholesterolemic subjects employing radioactive precursors, e.g. [3H]serine, [3H]glucose, and [14C]galactose. Compared to cells incubated with lipoprotein-deficient serum, maximum suppression (70-80%) of incorporation of [3H]glucose and [3H]serine into ceramide and LacCer occurred when the LDL concentration in the medium was 25 micrograms/ml medium, and addition of higher amounts of LDL (up to 500 micrograms/ml medium) to normal cells did not produce further suppression. In contrast, high density lipoproteins did not suppress the incorporation of [3H]glucose into lactosylceramide (LacCer) in normal cells. The incorporation of [14C] galactose into LacCer was also suppressed by LDL (50% suppression at a concentration of 100 micrograms/ml medium). In contrast, LDL modified by reductive methylation of lysine residues did not suppress the incorporation of [3H]glucose into LacCer and the incorporation of [3H]serine into ceramide, whereas, native LDL exerted a concentration-dependent suppression of [3H]serine incorporation into ceramide and sphingomyelin in normal cells. At high concentrations of LDL (50-500 micrograms/ml medium), the incorporation of [3H]glucose and [14C]galactose into LacCer in homozygous FH cells was stimulated approximately 2-fold. Maximum stimulation of [3H]serine incorporation into ceramides, LacCer, and sphingomyelin occurred at 100 micrograms LDL/ml medium. Our studies indicate that the endogenous synthesis of sphingolipids in normal renal cells is regulated by the LDL receptor. Modification of the lysine residues in LDL by reductive methylation results in the inability to suppress sphingolipid synthesis in normal cells. Lack of LDL receptors, as in the case of homozygous FH cells, results in the lack of suppression of endogenous sphingolipid synthesis.